2023
DOI: 10.1212/wnl.0000000000200567
|View full text |Cite|
|
Sign up to set email alerts
|

Gender Representation Among Physician Authors of Practice Guidelines Developed, Endorsed, or Affirmed by the American Academy of Neurology

Abstract: Background and ObjectivesTo assess American Academy of Neurology (AAN)–recommended Practice Guidelines (PGs) for equity in gender representation among physician authors.MethodsThis cross-sectional study included AAN-recommended PG publications from January 1, 2015, to December 31, 2020. Author degrees and gender were identified by 2 reviewers using the publication and/or online searches. Gender was determined from pronouns or photographs. Gender representation was compared with Association of American Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The issue of women physicians being particularly underrepresented on CPGs is consistent with the published literature. 2,3,[20][21][22][23][24][25][26][27][28][29][30] Even when there is an upward trend in the inclusion of women experts, this may not represent equitable inclusion across the specialty or disease topic. For example, a study evaluating the gender representation for CPGs published by the National Comprehensive Cancer Network found that the proportion of women on panels increased from 2013 to 2019 by 1.6% per year, and this rate was roughly equivalent to 1.0% per year previously observed among oncology trainees and full-time female hematology/ oncology faculty.…”
Section: Gendermentioning
confidence: 99%
“…The issue of women physicians being particularly underrepresented on CPGs is consistent with the published literature. 2,3,[20][21][22][23][24][25][26][27][28][29][30] Even when there is an upward trend in the inclusion of women experts, this may not represent equitable inclusion across the specialty or disease topic. For example, a study evaluating the gender representation for CPGs published by the National Comprehensive Cancer Network found that the proportion of women on panels increased from 2013 to 2019 by 1.6% per year, and this rate was roughly equivalent to 1.0% per year previously observed among oncology trainees and full-time female hematology/ oncology faculty.…”
Section: Gendermentioning
confidence: 99%
“…We want to thank the group of American Academy of Neurology (AAN) practice guideline (PG) leaders for their attention to our study, 1 but we find their complaints related to our work to be unfounded.…”
mentioning
confidence: 99%
“…In the Research Article previously titled “Gender Representation Among Physician Authors of American Academy of Neurology Clinical Practice Guidelines” by Ross et al, 1 several changes were made after online-first publication of the accepted manuscript before final publication. The article title was revised, along with the titles of Figures 1, 2, 3, and 4.…”
mentioning
confidence: 99%